Acute abdomen in pregnancy: a case series on clinical presentation and diagnostic dilemma - Abhirami, G. R.; Sathyavani, Chennaiahgari; Patil, Ravi N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Acute abdomen in pregnancy remains one of the most challenging situation in regard with the diagnosis and management. Pregnancy is a unique state in which the female body undergoes both anatomical and physiological changes which can pose a challenge in diagnosis. This may result in delay in management and increase in maternal and fetal morbidity and mortality. This study was to identify the spectrum of causes, the clinical presentation and diagnostic dilemma of acute abdomen in pregnancy. It was an observational study was done over a period of 3 years which included all the pregnant women who presented with acute abdomen. In this study, eighteen pregnant women presented with acute abdomen. Among the study group, 5.5%, 50% and 44.5% presented in first, second and third trimester respectively. The diagnosis included acute appendicitis in 11.1%, acute cholecystitis in 16.6%, acute pancreatitis in 16.6%, malrotation in 11.1%, uterine rupture 11.1%, rudimentary horn rupture in 22.4% and ovarian cyst torsion in 11.1%. The clinical presentation included pain abdomen (16.6%), pain abdomen and vomiting (44.4%), pain abdomen in shock (39%) and abdominal tenderness (33.3%). The diagnosis was confirmed with ultrasonography in 55.6%, 11.1% women required higher imaging like magnetic resonance imaging (MRI) and 33.3% women were diagnosed on table. Majority of them had good outcome, but there was one maternal mortality (6%). Diagnosis and treatment of acute abdomen in pregnancy should be individualized. Good clinical acumen is essential for ordering early diagnostic test in acute abdomen in pregnancy. Appropriate intervention should be undertaken at the earliest to reduce the maternal and fetal complications.